HUBUNGAN PENGETAHUAN DAN SIKAP PERAWAT TERHADAP KELENGKAPAN PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI RUANG RAWAT INAP RUMAH SAKIT UMUM DAERAH PROF. DR. W. Z. JOHANNES KUPANG - Risal Sinlaeloe (CHMK NURSING SCIENTIFIC JOURNAL, 2020)
Documentation of nursing care is evidence and reporting owned by nurses that are useful for clients and important for nurses as the responsibility and accountability of various problems experienced by clients in receiving nursing services. If something is done that is not written or documented then it is assumed not to have happened and poor nursing documentation can cause information about the client to be interrupted. Nurses' knowledge and attitudes are important in determining the completeness of nursing care documentation. The purpose of this study was to analyze the relationship between nurses' knowledge and attitudes with the completeness of nursing care documentation in the Inpatient Room of. Regional Hospital Prof. Dr. W. Z. Johannes Kupang. The design used in this study is the correlation with cross sectional design. The sampling technique used is total sampling with 41 respondents nurses. Knowledge and attitude data collection was carried out using a questionnaire, and the completeness of documentation of nursing care was carried out using observation sheets. The results of the study indicate that there is a relationship between knowledge and attitude with the completeness of documentation of nursing care, so it is suggested efforts to increase the knowledge and attitudes of nurses to support the implementation of nursing care documentation. Keywords : Knowledge and attitude of nurses, completeness of documentation of nursing care